Effectiveness of legal strategies to combat the crime of human trafficking - Martínez Franco, Pedro Alfredo (2019)
Objective. To determine the level of effectiveness of legal strategies that have been established to combat the crime of human trafficking in Huanuco, 2018. Methods. Deductive method was followed, because from observational and documentary analysis, inferences were obtained to evaluate the level of efficacy achieved. Quantitative approach was followed, because the collected data were calculated. These data were expressed in percentage terms for statistical analysis of the information. Level was descriptive and explanatory, since legal measures issued by Regional Government of Huanuco were taken into account, and actions carried out were described. Population comprised of 32 entities that are part of the Multisectoral Network to Combat Human Trafficking in Huanuco Region, and also habitants of the region. The sample consisted of all the entities that are part of the aforementioned network and, in addition, 80 habitants. Results. Central Government issues regulations that must be replicated in each of the regions with participation of the Regional Government and local government authorities from public administration sectors and civil society entities. However, the lack of budget and the lack of trained personnel are factors that impede the achievement of established goals. Conclusion. Effectiveness level of legal strategies to combat the crime of human trafficking in Huanuco is significant, during 2018. However, after knowing certain deficiencies that have not allowed the required efficacy. It is possible to get better results in the future.